Autoimmune polyglandular syndrome Type IIIB associated with immune thrombocytopenia, leukopenia, beta thalessemia trait, and language impairment - Bagri, Dhan; Sharma, Rambabu; Mathur, Priyanshu (Journal of Diabetes and Endocrine Practice, 2018)
Autoimmune Polyglandular Syndrome (APS) is characterized by presence of immune dysfunction of two or more endocrine glands and other non-endocrine organs. Only few cases of APS III associated with different immunological or genetic disorders have been reported. We present a 17-year old boy presented with easy fatigability, recurrent abdominal pain, pallor and language impairment; evaluated to have Autoimmune Thyroiditis, Megaloblastic Anemia due to vitamin B12 deficiency and Type 1 Diabetes Mellitus; with final diagnosis as APS IIIB with Immune Thrombocytopenia, leucopenia and Beta Thalessemia trait. The child requires lifelong monitoring of glandular functions and hormone replacement therapy for established glandular failure or failures. APS IIIB is as yet known to occur in middle aged women. It should be suspected in younger ages and diagnosed early to prevent the complications associated with the chronic endocrine deficiencies.
Keywords: Autoimmune polyglandular syndrome; language impairment; thalassemia